2013
DOI: 10.1123/jpah.10.6.910
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Recess Interventions to Increase Physical Activity

Abstract: A number of simple, low-cost strategies can be implemented to maximize the amount of recess time students are allotted. Long-term follow-up studies are warranted for each of the recess strategies identified to be effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
71
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 29 publications
(201 reference statements)
4
71
1
2
Order By: Relevance
“…through active travel, physical education (PE) and recess. Intervention studies aimed at promoting PA in all these settings have shown promising results (Lonsdale et al, 2013; Larouche et al, 2014; Ickes et al, 2013). However, because it is already compulsory in most schools and does not compete with academic interests (Ickes et al, 2013), recess might be a particularly attractive arena for PA promotion.…”
Section: Introductionmentioning
confidence: 99%
“…through active travel, physical education (PE) and recess. Intervention studies aimed at promoting PA in all these settings have shown promising results (Lonsdale et al, 2013; Larouche et al, 2014; Ickes et al, 2013). However, because it is already compulsory in most schools and does not compete with academic interests (Ickes et al, 2013), recess might be a particularly attractive arena for PA promotion.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in Europe and Australia found that recess physical activity was associated with aspects of the school physical environment, such as large play space [14], adequate equipment [14,15,16,17,18,19,20], and playground marking [19,21,22]. In addition, playground-related environmental interventions such as equipment provision, multicolor marking, and clear division by activity type have been reported to be effective in promoting physical activity during recess [23,24,25,26,27]. These studies have also found that gender differences play a role in the effectiveness of the interventions.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in MVPA is in contrast to VanKann's intervention study (13) that showed positive LPA outcomes but no effect on MVPA. In a review, Ickes et al (21) reported that a variety of recess interventions has been found to be effective in increasing PA. However, the small number of intervention studies does not allow to establish conclusive effects on children's recess PA (22) and most of them lasted less than 12 months.…”
Section: Discussionmentioning
confidence: 99%